Projection invariant t-Baer and related modules - Kara, Yeliz (Ukrains’kyi Matematychnyi Zhurnal, 2023)
UDC 512.5 We investigate the concepts of projection invariant t-extending modules and projection invariant t-Baer modules, which are generalized to those π-extending and t-Baer notions, respectively. Several structural properties are obtained and some applications are developed. It is proved that the π-t-extending modules and π-t-e. Baer modules are connected with each other. Moreover, we obtain a characterization for π-t-extending modules relative to the annihilator conditions.